PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SEKOLAH DASAR NEGERI DALANGAN 02 KABUPATEN SUKOHARJO TAHUN PELAJARAN 2024/2025 - Fera Magareta; Dwi Anggraeni Siwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve motivation and mathematics learning outcomes through the application of the Project Based Learning (PjBL) model in grade IV students of SD Negeri Dalangan 02, Tawangsari District, Sukoharjo Regency. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles. Each cycle consists of planning, action, observation, and reflection. Data were collected through tests, motivation questionnaires, observation, and documentation. The results of the study showed that the application of the PjBL model can increase mathematics learning motivation with a percentage of 40.64% in the low category in the pre-action, increasing to 71% in the high category in cycle I and increasing again to 79.71% in the high category in cycle II. The average learning outcomes increased from 56% in the pre-cycle to 87% in cycle I and increased again to 92% in cycle II. The research results obtained in cycle II have achieved the success indicator, so the research did not continue to the next cycle. Thus, the PjBL model has proven effective in improving students' motivation and mathematics learning outcomes.